A critical evaluation of conflict resolution techniques: from problem-solving workshops to theory - Du Pisani, André (Department of Political Studies, 2016)
The object of this study is to present a comparative analysis of the system of problem-solving workshops and associated conflict resolution techniques exemplified in the work of John W Burton and Leonard Doob and their associates. The approach has been to structure the research as a methodological critique of the Burton and Doob models, with special consideration given to their respective domain assumptions, internal logic, methodology, process and prescriptive dimensions. Informed by the assumption of the universality of conflict, the study begins by examining the particular strengths and weaknesses associated with Burton and Doob's work. The approach is descriptive-analytical and sets out to isolate, identify and describe the salient features of the problem-solving approach followed by the two authors. Specific case studies used by them have been subjected to critical analysis. The basic notion of problem-solving and its relevance to conflict analysis and resolution is also explored in some detail. In arriving at a conclusion, the study suggests that problem-solving workshops have specific strengths, notably in the area of conflict analysis as well as in influencing individual perceptions and competing value positions. Certain shortcomings in the theoretical and practical utility of this approach, however, could be overcome, in the author's opinion, by giving attention to the area of third party intervention, notably in assessing the variables affecting the process, such as the time sequence, the structure of the discussion format, and the application of specific techniques. In the final analysis, it is agreed that these problem-solving workshops can serve as a useful analytical tool in contemplating the dynamic of conflict relationships and behaviour. Their theoretical and practical utility, but remain inherently limited unless they are integrated with a broader body of literature on bargaining and third party intervention. The study concludes with the observation that despite an extensive and growing body of literature on conflict, the practice of third party intervention - especially within the workshop setting - has only recently been studied in depth. It is in this respect that this study hopes to be of some practical value especially in the case of a deeply divided society such as South Africa.